Economic Diversification and the Urban Image; Changing the Narrative on Street Vending - MUHAMMAD K BALARABE; ABDULSALAM SHEMA IBRAHIM; MARYAM AHMAD (Journal of Contemporary Urban Affairs, 2019)
Street vending is a dynamic phenomenon of network of events, socio-economic and cultural factors while remaining a narration of place. At the metropolitan level, the narrative is negatively skewed towards street vending and its aesthetic reality, contemporaneously exploring hostile environmental interventions within the informal sector. This paper attempted to explore a counter-narrative asking; based on aesthetic experience, can the “desired” urban image to be achieved by allowing street vendors proliferate in public spaces? This question was asked within the scope of the political-economy of diversification in Nigeria. The paper argued that, around public spaces such as parks and sidewalks, the precarious nature of vending activities lead to their diffidence in upgrades to stalls, tables and kiosks. With pictures from spaces that appear to approve of street vending tacitly, a pattern of upgrades in vending apparatus and kiosks were established. This paper proposes an integrative model of passive, active and tacit support that is required to influence the discourse of vending activities within the context of urban images produced in Nigerian. In conclusion and using sing Gouverneur (2014) concepts of receptors and transformers, this paper revealed that potential existing parks within a dense urban area could serve as transformers, creating an urban image that defies that “out of place” narrative associated with vendors.